Pengaruh Profitabilitas Terhadap Nilai Perusahaan Pada Sub Sektor Rokok Yang Terdaftar di BEI Periode 2021-2023 - Putri, Ananda; Amran, Indri Ardhana; Muttia, Ririn; Basri, Musdalifah; Aljabar, Muhammad (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2024)
This study aims to analyze the effect of profitability, as measured by Return on Assets (ROA) and Return on Equity (ROE), on the value of companies in the cigarette sector listed on the Indonesia Stock Exchange. The background of the study shows that although high profitability can increase investor confidence and company value, many companies in this sector face challenges such as raw material price volatility and the impact of the pandemic. The research method used involves collecting data from cigarette companies listed on the Indonesia Stock Exchange during the period 2021-2023 using a purposive sampling technique. The results of the analysis show that ROA has a negative effect on company value, while ROE has a significant positive effect. The average Tobin's Q value shows large variations between samples, and statistical analysis shows that 85% of the variation in company value can be explained by ROA and ROE. This study concludes that profitability has a significant effect on company value, with companies with high profitability tending to have better market value